Running as a Social Practice: Communication Practices and Identity Formation in Urban Running Communities - Tita Melia Milyane; Dasrun Hidayat; Nofha Rina; Fatmah Hulaibi (UPT Publikasi Ilmiah UNISBA, 2026)
While urban running has surged in popularity, existing studies often focus on the physical health benefits or elite athletic performance, leaving a gap in understanding how novice runners navigate the transition from casual exercise to a structured social identity. This study addresses this gap by examining how communication practices within urban running communities facilitate the formation of values, lifestyles, and identities among beginners. A phenomenological approach is employed to capture the essence of the lived experience and the subjective meanings novice runners attach to their social interactions, providing a deeper understanding of identity construction that quantitative methods cannot reach. Data were gathered through indepth interviews and participant observation with members of the Indorunners Playon Jogja community, followed by thematic analysis. The findings reveal that involvement in these communities is a transformative process where running evolves from a sporadic activity into a disciplined daily routine and a core component of self management. Communication manifested through face to face social support and digital media engagementacts as the primary catalyst in strengthening a sense of belonging and solidifying a new runner identity. Theoretically, this study contributes to the field of communication science by positioning urban sports as a dynamic arena for social practice and identity negotiation. Practically, it offers insights for community organizers and urban health practitioners on leveraging social communication to sustain long term physical activity and community engagement among the urban populace.